1989
DOI: 10.1002/mrd.1120240404
|View full text |Cite
|
Sign up to set email alerts
|

Devlopment of chimaeric two‐cell mouse embryos produced by allogenic exchange of single nucleus from two‐ and eight‐cell embryos

Abstract: Synchronous or asynchronous chimaeras were produced by transplanting a single nucleus of two- and eight-cell embryos from CD-1xCD-1 or BALB/CxBALB/C albino strains into one enucleated blastomere of a late F1 (C57/BLxCBA) x F1 two-cell embryo. The cytoplasmic volume of the blastomere was reduced in some instances by 50%. These chimaeric embryos were cultured in vitro and transferred to pseudopregnant recipients. The distribution of each component to the pups and to the day-10 embryos after transfer to recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Synchronization of the cell cycle between a donor nucleus and recipient cytoplasm is important for pronuclear and nuclear exchange (Smith et al, 1988(Smith et al, , 1990, nuclear transplantation of fetal germ cells (Kato & Tsunoda, in press) and the production of chimaeric embryos (Kono et al, 1989). The observation that nocodazole can synchronize cell division of two-cell mouse embryos up to the four-cell stage may be applicable to such studies.…”
Section: Resultsmentioning
confidence: 99%
“…Synchronization of the cell cycle between a donor nucleus and recipient cytoplasm is important for pronuclear and nuclear exchange (Smith et al, 1988(Smith et al, , 1990, nuclear transplantation of fetal germ cells (Kato & Tsunoda, in press) and the production of chimaeric embryos (Kono et al, 1989). The observation that nocodazole can synchronize cell division of two-cell mouse embryos up to the four-cell stage may be applicable to such studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, no chimeric conceptuses were obtained from embryos reconstituted with TE cells or ICM cells. Chimeric mice were produced by nuclear transplantation of single nuclei from 8-cell embryos into an enucleated blastomere of a 2-cell embryo [8]. Failure to demonstrate pluripotecy of ICM cells with this procedure may have been due to too large a difference in developmental stage between the donor cell and recipient 2-cell embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura and Tsunoda [6] have reported that mouse chimeras were produced by synchronous allogenic exchange of a single nucleus at the 2-cell stage. This procedure has also produced chimeraes from asynchronous embryos up to the 8-cell stage [7,8]. …”
mentioning
confidence: 99%